Membrane Proteins: Structure, Function and Motion (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Membrane proteins are essential for the diverse biological functions of the cells and intercellular communication in living organisms. With the recent developments in the methodologies, the research on membrane proteins has been undergoing a major transformation. In this informative book, the biological and dynamic behaviour of membrane proteins are introduced, discussed, and reviewed by some of the leading researchers in the field. The main objective of this compendium is to present the recent research in the fundamental and advanced concepts and methodologies used for studying membrane proteins. Membrane protein purification and reconstitution, protein–lipid interaction, ion/substrate transport, conformational and functional dynamics, the interaction of infectious agents, cell death, and organelle morphology are among the topics that are covered. This reprint is intended for a broad range of novice and experienced scientists with different levels of experience, from biophysicists and biochemists to microbiologists, cell biologists, and physiologists.